Adaptive phase matching probe-injection technique for enhancement of Brillouin scattering signal. (1st August 2017) - Li, Hongwei; Shi, Guangyao; Lv, Yuelan; Zhang, Hongying; Gao, Wei
Highlights: An adaptive phase-matching probe-injection technique is proposed for the first time. Any weak stokes signal in its APM range can be enhanced instantly by SBA. The SNR of Brillouin gain spectrum is effectively improved. The feasibility of this technique is demonstrated experimentally and theoretically. Abstract: We report on a simple and efficient method for enhancing Brillouin scattering signal, i.e., adaptive phase matching (APM) probe-injection technique. In this technique, a low-polarization broad-spectrum probe wave is injected opposite to the pump, which can enhance any stokes signal in its APM range instantly by selective stimulated Brillouin amplification. With advantages of simple scheme, real-time multi-signal enhancement and sweep-free measurement, this technique has a great potential for improving the signal-to-noise ratio of Brillouin gain spectrum in the Brillouin scattering application systems.